The Impact of Immunization and Use of Oseltamivir on Influenza-Related Hospitalizations: A Population-Based Study - Vassilis Athanassoglou; Lauren A. Wilson; Jiabin Liu; Jashvant Poeran; Haoyan Zhong; Stavros G. Memtsoudis (SAGE Publishing, 2021)
Background As the COVID-19 pandemic continues into flu season, it is critical to minimize hospitalizations to maximize capacity and preserve critical care resources. We sought to identify risk factors for influenza-related hospitalization, specifically the role of immunization and oseltamivir prescriptions. Methods Patients with influenza diagnoses were identified from the MarketScan database (2014-2018). Primary risk factors of interest were an influenza vaccination within 6 months prior to infection and oseltamivir prescriptions (filled on the day diagnosis, the following day, or 2-5 days). A multivariable logistic regression model was run to identify risk factors for influenza-related hospitalizations within 30 days of diagnosis. Results Among 2 395 498 influenza infections, 0.27% were hospitalized. Of those prescribed oseltamivir the day of diagnosis, 0.13% were later hospitalized, compared to 0.67% among those who filled prescriptions the following day and 11.8% when filled within 2 to 5 days. Upon adjustment, oseltamivir prescriptions filled on the day of diagnosis were associated with significantly decreased odds of hospitalization (OR 0.51 CI 0.48-0.55). Prescriptions filled within 1 to 5 days of diagnosis were associated with significantly increased odds of hospitalization (1 day OR 2.01 CI 1.81-2.24; 2-5 days OR 34.1 CI 31.7-36.6). Flu vaccination was associated with a lower odds for hospitalization (OR 0.84 CI 0.74-0.95). Conclusions We recommend oseltamivir be prescribed to patients when they first present with influenza-like symptoms to reduce the burden on the healthcare system. We also identified reduced odds of hospitalization associated with influenza vaccination, which is already well established, but particularly important this coming flu season.